ANALYSIS OF INDONESIAN LANGUAGE ERRORS IN OFFICIAL LETTER AT THE KAWALI VILLAGE OFFICE - Angelina Sepiani Kusmawati; Milna Widya; Eulis Siti Nurallawiah; Aveny Septi Astriani (Media Inovasi Pendidikan dan Publikasi, 2023)
The purpose of this study is to examine phonological, morphological, syntactic, and semantic problems found in official correspondence from the Kawali Village Office. Aside from that, the research's objective is to offer guidance and fix mistakes in official correspondence, particularly at the Village Office. Mastery. Qualitative descriptive methodology is the research strategy employed. The following are the research's findings: First, phonological, morphological, syntactic, and semantic faults are among the types of language errors identified. Second, the domain of semantics is where the most mistakes are made. Third, the letter's structure was written incorrectly. Errors in official letter writing at the Kawali Village Office in Indonesia are caused by four factors: 1) village officials may employ pre-existing templates, which leads to inaccuracies in Indonesian. 2) There is no training in letter writing; 3) a need for improvement in reading and writing interest.